Einführung und Evaluation eines Stationsapothekers in der Neurochirurgie: Projektarbeit im Rahmen der Weiterbildung Klinische Pharmazie - Pauly, Anne; Busse, Marika; Koch, Sonja; Dörje, Frank; Rammensee, Rudolf; Buchfelder, Michael (Krankenhauspharmazie, 2019)
2.5 full-time positions for clinical pharmacists were approved by the hospital board for a two-year project (01.01.2015 - 31.12.2016). The clinical pharmacists were deployed to different clinics with the objectives to support safety of medication therapy and achieve a pharmacoeconomic impact. A 0.45 part-time position was assigned to the neurosurgical department. During the two-year project, an evaluation period of one year was defined to assess drug related problems, pharmaceutical inquiries and pharmacoeconomic interventions. The results of the evaluation period were presented to the neurosurgical clinic management along with a final survey among the physicians and nursing staff. The neurosurgical directors decided to maintain a 0.25 clinical pharmacist position, hence a safe, efficacious and economic drug therapy can be ensured in the neurosurgical department.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Clinical pharmacist; Drug related problem; Medication management; Medication safety; Neurosurgery